Augustine on fate and astrology revisited - Andoková Marcela (Belgrade Philosophical Annual)
In De civitate Dei V,1-11 revaluating Stoic fate, Augustine develops a new understanding of fate which is changed from Stoic rational order to a voluntary order attributed to the will of God and eternally spoken by God. In these chapters, apart from the presentation of philosophical views on this topic, the bishop of Hippo pays particular attention to the refutation of astrological practices which, at his time, were very common in the Roman Empire not only among the Roman elite but it permeated various strata of society as well. Ordinary people sought the advice of astrologers for personal matters such as marriage, business ventures, and health. Moreover, astrology and other forms of divination often intersected with religious beliefs and practices. The Romans were deeply superstitious, and astrology provided a means of understanding and influencing fate. Although at his younger age, Augustine had been strongly influenced by astrology, as becomes clear particularly in his Confessions, later as a bishop he was fighting against these practices not only in his theoretical works but also in his sermons and exegetical homilies. The aim of this article is therefore to see how Augustine's views of astrology and fate presented especially in his homilies on Johns's Gospel (In Iohannis Evangelium tractatus 1-16) fit into his discussion on God's foreknowledge, human free will and responsibility summarised in the opening chapters in Book V of his De civitate Dei.